Pengaruh Pembiayaan Mudharabah, Murabahah, Musyarakah, Ijarah Terhadap Profitabilitas Pada Pt. Bank Bri Syariah Malang Periode 2015 – 2019 - Alya Novia Chamidah; Muhammad Ridwan Basalamah; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine the effect of mudharabah, murabahah, musyarakah, ijarah financing on the profitability of case studies at PT. Bank BRI Syariah Malang 2015-2019 period. In this study, there are 4 (four) independent variables, namely mudharabah, murabahah, musyarakah, ijarah financing. And the dependent variable in this study is profitability which is calculated using the return on asset ratio. Population and sample in this study PT. Bank BRI Syariah Malang. The data collection method used is documentation with reference to the bank's annual financial statements. The data analysis technique used in this study is multiple linear regression. The results of the research simultaneously state that the financing of mudharabah, murabahah, musyarakah, ijarah has a positive and significant effect on profitability. Meanwhile, partially mudharabah financing has a negative and significant effect on profitability. Murabahah and musyarakah financing has a positive and significant effect on profitability. Ijarah financing has a positive and insignificant effect on profitability. Keywords: mudharabah, murabahah, musyarakah, ijarah financing, profitability